Peningkatan Pengetahuan tentang Jenis Penyakit di Usia Lansia pada Kelompok Lansia - Ni'matul Ulya (LPPM Akbid Harapan Ibu Pekalongan, 2021)
The success of national development, especially national development in the health sector, can be seen from the increasing life expectancy of the Indonesian people. Eleven percent of the world's 6.9 billion population are elderly. Indonesia experienced an increase in the number of elderly people from 18 million (7.56%) in 2010, to 25.9 million (9.7%) in 2019, and is expected to continue to increase where in 2035 to 48.2 million people (15.77%). The elderly are identical with various decreases in health status, especially physical health status. In general, it is quite difficult to recognize health problems early on, especially diseases that usually arise in old age. Health problems can be prevented with a healthy lifestyle, so it is necessary to increase knowledge about diseases that commonly occur in old age. The method used in this community service activity is through a lecture to the Elderly Aisyiyah group in Pekalongan City. The results of this activity increased knowledge of the elderly by 36.3% for the causes of rheumatic disease, 27.3% for rheumatic symptoms and 30.3% in the diet of rheumatic diseases; 27.3% for the causes and diet of gout, and 36.3% for the symptoms of gout; 33.3% for causes of hypertension, 36.3% for symptoms and 27.3% for hypertension disease diet; as much as 27% about the cause of Diabetes Mellitus (DM), 27.3% symptoms and 30.3% for diets with diabetes mellitus.